Muonium behavior in N-acetylglycine-N-methylamide - Pant, Amba Datt (BIBECHANA, 2021)
In muon spin rotation and relaxation (mSR) method, theoretical work using first-principles calculations helps to understand the stopping sites and charge states of muon in the sample materials. To support the mSR measurement on protein and DNA, a systematic first-principles study starting from the constituents of the protein has been performed. In this work, the behavior of muonium (Mu = m+e-, bound state of a muon and an electron which is like a light isotope of H atom with similar chemical properties) in a N-acetylglycine-N-methylamide (AGMA), a part of peptide bond, is presented. It is found that the stopping site of Mu is around O of unsaturated bonds between C and O in the AGMA. Further calculations towards whole protein and DNA will be performed to support mSR studies.BIBECHANA 18 (2) (2021) 138-142